Reading speed and eye movement pattern in artificial central scotoma stimulations / Nur Zahirah Mohamaad Zahir - Mohamaad Zahir, Nur Zahirah (Faculty of Health Sciences, 2015)
To determine and compare the reading speed and eye movement pattern with four different locations of artificial central scotoma in normally sighted participants. Materials and methods: Eleven normally sighted participants with age range from 23 to 26 years old were recruited in this study. After pass all the screening procedure, the participants were then proceed to eye movement and reading speed measurement in normal condition and with 4 artificial central scotoma stimulations. Scotoma size was 10° which equivalent to 1cm in height. The participants were asked to read the Malay reading passage at random order aloud. The time taken to read each chart was recorded and any reading error made was noted. The reading speed was measured in words per minute (wpm). The eye movement pattern during reading was automatically captured using Three-D Videoculagraphy (VOG). The eye movement was measured in term of number of fixations and number of regression. Results: The reading speed showed significant difference between four different locations of artificial central scotoma stimulation, F(4,54)=3.17, p=0.02. No significant different was showed in eye movement during reading which obtained F(4,54)=0.61, p=0.65 and F(4,54)=0.90, p=0.47 for number of fixations and number of regression, respectively. Conclusion: The presence of artificial central scotoma stimulation affects the reading speed but not the eye movement patterns in term of number of fixation and number of regression.